Leadership and political culture: a brief look at the Malaysian political landscape / Nasrudin Mohammed - Mohammed, Nasrudin (Universiti Teknologi MARA, Shah Alam, 2007)
Since 1930s, political discourses and literature were concentrated on the nature of leadership. Back then - and remained to be so though with more variables are considered - individual personal traits, styles, and behaviours were the main elements that has attracted and characterise all types of leader. Perhaps Bolman & Deal's (1991) view would best describe who political leaders are when they say that, "Political leaders clarify what they want and what they can get; they assess the distribution of power and interests; they build linkages to stakeholders; use persuasion first, then use negotiation and coercion only if necessary."